Evolution of virulence in eukaryotic microbes - Sibley, L. David; Howlett, Barbara J.; Heitman, Joseph (Wiley-Blackwell, 2012)
"Combines advances in understanding virulence and evolution in three distinct fields; oomyctes, fungi and protozoan parasites - The first book to synthesizes advances in functional and comparative genomics represented in primary scientific literature for this topic. - Summarizes genetic tools in a diverse set of pathogenic organisms"--